Sistem pengurusan bersepadu: satu pengenalan - Kadir Arifin,; Jamaluddin Md. Jahi,; Ismail Bahari,; Abd Rahim Md Nor,; Abu Bakar Che Man, (Environmental Management Society, Malaysia, 2005)
The implementation of management systems such as ISO 9001:2000, ISO 14001:1996 and OHSAS 18001:1999 is a requirement for any organization in order to ensure business sustainability. This is because organizations will enjoy numerous benefits that the systems could offer such as cost reduction, improved corporate image and to stay competitive. Besides these advantages, however, there are several drawbacks if the systems are implemented separately. Among these drawbacks include redundant work, cost incurred, time consuming and additional workload due to the redundancy in the requirements of the three systems. Therefore, organizations have to find alternatives to deal with these situations. The emergence of the Integrated Management System (IMS) is seen to be the best solution for the organizations. This is due to IMS itself has its own advantage mainly by the elimination of the redundancy in the requirements of the system. This paper reveals the problems encountered when the systems are implemented separately, and how IMS could offer solutions to the organizations